Peningkatan Hasil Belajar IPA Materi Mengidentifikasi Fungsi Organ Pencernaan Manusia Dan Hubungannya Dengan Metode Pembelajaran Demonstrasi Melalui Media Gambar Siswa Kelas V SD - Wuranti; Dina Syaflita (Indonesian Journal of Integrated Science and Learning, 2023)
This research intends to obtain data on improving science learning outcomes on material identifying the function of human digestive organs and its relationship with demonstration learning methods through drawing media for fifth grade elementary school students. This research includes classroom action research with the subject being 12 fifth grade elementary school students. The final results of this improvement will be completed if the student's learning scores increase and reach the KKM. The results of research improvements show that the integrity of students' science learning increases after carrying out cycle activities. In the cycle before action was given, there were 4 students (33%) who achieved the KKM with an average score of 60, while after cycle 1 stage, there were 9 students (75%) who obtained the KKM with an average of 70. In cycle 2 stage this happened. an increase of 11 students (83%) obtained an average KKM score of 75. The results have achieved the author's desired objectives and show an increase in student mastery in science subjects.